Local agrarian societies in colonial India : Japanese perspectives - Robb, Peter (Peter G.); Sugihara, Kaoru; Yanagisawa, Haruka, 1944- (New Delhi : Manohar, 1997)
Papers presented at a conference held in July 1992.
Originally published: Richmond, Surrey : Curzon Press, 1996. (Collected papers on South Asia ; 11).
Includes bibliographical references.
Keywords: Agriculture -- Economic aspects -- India; Famines -- India; India -- Rural conditions; India -- History -- British occupation, 1765-1947.